CSR decoupling within business groups and the risk of perceived greenwashing - Bothello, Joel; Ioannou, Ioannis; Porumb, Vlad‐Andrei; Zengin‐Karaibrahimoglu, Yasemin (Strategic Management Journal, 2023)
Abstract Research Summary Given the growing legitimacy of corporate social responsibility (CSR), many firms engage in symbolic communication to showcase CSR without undertaking commensurate substantive actions. This “CSR decoupling” can create a risk of perceived greenwashing, which, in turn, may negatively affect a firm's performance. In this study, we explore an unexamined antecedent of decoupling: interfirm affiliation. Specifically, we use the structure of Business Groups (BGs) to investigate CSR decoupling across rather than within firms. We find that apex firms within a group are more likely to engage in CSR decoupling compared with non‐apex firms and, importantly, are partially shielded from greenwashing perceptions by the market. Our research contributes to the literatures on decoupling, perceived greenwashing, and the role of BGs and their CSR practices. Managerial Summary Companies that engage in symbolic communication about corporate social responsibility (CSR) without substantive actions risk being perceived as “greenwashers,” a perception that harms firm performance. Our study demonstrates how, in certain contexts where firms are affiliated with others, this may not occur. For instance, apex firms within Business Groups (BGs)—where firms are interconnected through equity and social relationships—can report on the CSR actions of non‐apex affiliates without providing commensurate substantive actions of their own. Importantly, the control and coordination abilities of these apex firms protect them from greenwashing perceptions. This study, therefore, demonstrates the role of BGs in shaping CSR practices and provides insights for managers to understand the potential risks and benefits of affiliations within BGs.